The Thirteenth Marcel Grossmann Meeting 2015
DOI: 10.1142/9789814623995_0472
|View full text |Cite
|
Sign up to set email alerts
|

General Relativistic and Newtonian White Dwarfs

Abstract: The properties of uniformly rotating white dwarfs (RWDs) are analyzed within the framework of Newton's gravity and general relativity. In both cases Hartle's formalism is applied to construct the internal and external solutions to the field equations. The white dwarf (WD) matter is described by the Chandrasekhar equation of state. The region of stability of RWDs is constructed taking into account the mass-shedding limit, inverse β-decay instability, and the boundary established by the turning points of constan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…As relatively few BDs are known and ages are difficult to constrain empirically, we rely on theoretical models to determine their luminosity L BD and effective temperature T ef f . Two standard models are available (Burrows et al 1997;Baraffe et al 2003) and their results are shown in Fig. 2.…”
Section: Brown Dwarf Coolingmentioning
confidence: 99%
See 1 more Smart Citation
“…As relatively few BDs are known and ages are difficult to constrain empirically, we rely on theoretical models to determine their luminosity L BD and effective temperature T ef f . Two standard models are available (Burrows et al 1997;Baraffe et al 2003) and their results are shown in Fig. 2.…”
Section: Brown Dwarf Coolingmentioning
confidence: 99%
“…BDs are objects that are not massive enough to produce the central pressures necessary to fuse hydrogen into helium. Nonetheless, BDs can support an HZ as their slow contraction converts gravitational energy into heat (Burrows et al 1997; Baraffe et al 2003). The habitability of planets about BDs has received less attention than habitability of planets orbiting hydrogen-burning stars, as a) relatively few are known, b) it is unknown if planets can form around them, and c) they are very faint.…”
Section: Introductionmentioning
confidence: 99%
“…Summarizing those results: they showed that the rotation can have astrophysical implications to Soft-Gamma Repeaters and Anomalous X-Ray Pulsars, rotation can also uplift slightly the maximum stable mass configuration and they also showed that the spin-up and spindown eras are different for sub and super-Chandrasekhar WD. In addition, in [31] the authors compare the results of general relativistic uniformly-rotating WD with uniformly-rotating Newtonian WD. In light of uniformlyrotating case the minimum rotation period is about the same in both cases (general relativistic and Newtonian) and the general relativistic maximum mass is slightly below the Newtonian maximum mass.…”
mentioning
confidence: 99%
“…This EoS is one of many stiff equations of state which are in accordance with the observational constraints on NSs [69]. The degenerate electron gas EoS was employed for the WD matter [81,82] as it is the simplest EoS.…”
Section: Rotating White Dwarfs and Neutron Starsmentioning
confidence: 87%